Factors Affecting Entrepreneurial Capacity Building of Smallholder Coffee Farmers in East Java Province - Sudarko Sudarko; Sumardjo Sumardjo; Anna Fatchiya; Prabowo Tjitropranoto (Indonesian Coffee and Cocoa Research Institute, 2020)
The income of smallholder coffee farmers can be increased by optimizing the added value of the product through increased entrepreneurial capacity. Coffee farmers need to adopt innovations and new approaches that are more sustainable with organic farming systems. The purposes of this study are; (1) identifying differences in characteristics, support of government extension services, private extension agents, and environmental support for smallholder coffee farmers and (2) analyzing the effect of characteristics, government extension services, private extension agents, and environmental support on the entrepreneurial capacity of smallholder coffee farmers. This study was carried out at Arabica Coffee Center in Bondowoso Regency and Robusta Coffee Center in Malang Regency, East Java from August to October 2019. Data were collected through interviews with questionnaires in a total of 376 smallholder coffee farmers. Data were analyzed using descriptive (SPSS) and inferential statistics (structural equation model/SEM analysis using Smart PLS). The results of research showed that non formal education and roles of private extension agents were found to be low. Moreover, motivation, government extension support, environmental support, and entrepreneurial capacity of smallholder coffee farmers were categorized as moderate. Factors significantly influenced entrepreneurial capacity of coffee farmers included: characteristics of farmers, government extension support, roles of private extension agents, and environmental support. The role of government to strengthen private extension agents is possible through partnership between coffee farmers, government and exporter or private sectors.